2018
DOI: 10.1186/s12939-018-0751-y
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of health status, health seeking behaviour and healthcare utilisation of low socioeconomic status populations in urban Singapore

Abstract: IntroductionIt is well-established that low socioeconomic status (SES) influences one’s health status, morbidity and mortality. Housing type has been used as an indicator of SES and social determinant of health in some studies. In Singapore, home ownership is among the highest in the world. Citizens who have no other housing options are offered heavily subsidised rental housings. Residents staying in such rental housings are characterised by low socioeconomic status. Our aim is to review studies on the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 25 publications
(53 reference statements)
4
86
0
1
Order By: Relevance
“…32,[35][36][37] Several factors beyond SES may explain the ethnic disparity in utilizing eyecare services in our study, such as adaptation to vision loss, health beliefs, and behaviors, illness perceptions, use of alternative medicine, coping skills, social support, and minority status in Malays compared to Chinese and Indians, all of which vary according to religious and cultural backgrounds. [38][39][40][41][42] In a previous report by our group, we found that a higher proportion of Malays compared to Chinese or Indians had undiagnosed eye diseases, such as glaucoma, DR, and vision-threatening DR, [19][20][21]25 suggesting that Malays take a more passive approach to disease management compared to their ethnic counterparts, consequently leading to low utilization of eyecare. More qualitative and quantitative research is needed to better understand why Malays have lower utilization of eyecare services and are more likely to find glasses less affordable.…”
Section: Discussionmentioning
confidence: 99%
“…32,[35][36][37] Several factors beyond SES may explain the ethnic disparity in utilizing eyecare services in our study, such as adaptation to vision loss, health beliefs, and behaviors, illness perceptions, use of alternative medicine, coping skills, social support, and minority status in Malays compared to Chinese and Indians, all of which vary according to religious and cultural backgrounds. [38][39][40][41][42] In a previous report by our group, we found that a higher proportion of Malays compared to Chinese or Indians had undiagnosed eye diseases, such as glaucoma, DR, and vision-threatening DR, [19][20][21]25 suggesting that Malays take a more passive approach to disease management compared to their ethnic counterparts, consequently leading to low utilization of eyecare. More qualitative and quantitative research is needed to better understand why Malays have lower utilization of eyecare services and are more likely to find glasses less affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the health system of many countries, the rights of citizens in health affairs are well observed in the laws of the health system. However, the identified weaknesses in this assessment are weaknesses in participation and consensus orientation, justice and equity in determining community needs, responsiveness and clarity, the quality and efficiency of provided services and responsibility (33). Several studies have shown that the health system faces numerous challenges in many countries and requires major changes in governance method.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we can mention to some items such as: lack of clarity of information due to the lack of proper infrastructure for electronic health filing, use of inappropriate hardware, existence of various software systems in the hospital and the lack of unified data, weakness in the quality of primary health care and referral system, lack of clinical guidelines, lack of appropriate responsiveness at all levels of the health system, inadequate ability of staff in providing services, lack of transparency of programs and strategies of the ministry of health, weakness in the development of the attitude of intra-sectorial cooperation at different levels of the health system, weakness in the decision-making and policy making system due to lack of community participation, weakness in attracting the participation of the public to develop and implement the health system policy, lack of adaptation of annual budgeting with development programs, etc. (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…All PCN clinics are CHAS enabled. More tiered subsidy schemes may motivate low SES patients to adhere to management plans and seek appropriate care [69]. Despite the enhancements made to CHAS to encourage Singaporeans to shift their care from polyclinics to the private GPs, our participants re ected that the CHAS quantum is insu cient to drive that behaviour.…”
Section: Discussionmentioning
confidence: 89%